Pengaruh Citra Merek dan Ulasan Pelanggan Terhadap Keputusan Pembelian di Aplikasi Shopee: Studi Pada Mahasiswa Institut Teknologi Dan Bisnis Kristen Bukit Pengharaapan - Philip Invokavid Agust Four; Yusak Prakoso (Jurnal Minfo Polgan, 2026)
“This study aims to analyze the influence of brand image and customer reviews on purchasing decisions on the Shopee platform. The study employs a quantitative approach. The research population consists of 280 students from the Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, with a sample of 74 respondents determined using the Slovin formula. Data analysis is conducted using multiple linear regression. The results indicate that both brand image and customer reviews have a positive and significant effect on purchasing decisions. These findings suggest that brand perception and information derived from customer reviews are key factors in shaping consumer purchasing decisions in the e-commerce context.”